Life, death and growing up on the western front - Fletcher, Anthony (Yale University Press, 2013)
"This book was inspired by the author's discovery of an extraordinary cache of letters from a soldier who was killed on the Western Front during the First World War. The soldier was his grandfather, and the letters had been tucked away, unread and unmentioned for many decades. Intrigued by the heartbreak and history of these family letters, Fletcher sought out the correspondence of other British soldiers who had volunteered for the fight against Germany. This resulting volume offers a vivid account of the physical and emotional experiences of seventeen British soldiers whose letters survive. Drawn from different regiments, social backgrounds, and areas of England and Scotland, they include twelve officers and five ordinary "Tommies." Â The book explores the training, journey to France, fear, shellshock, and life in the trenches as well as the leisure, love, and home leave the soldiers dreamed of. Fletcher discusses the psychological responses of 17- and 18-year-old men facing appalling realities and considers the particular pressures on those who survived their fallen comrades. While acknowledging the horror and futility the soldiers of the Great War experienced, the author shows another side to the story, focusing new attention on the loyal comradeship, robust humor, and strong morale that uplifted the men at the Front and created a powerful bond among them"--Publisher's description.